2007
DOI: 10.1161/atvbaha.107.143248
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Fibrinolytic Capacity Predicts Future Adverse Cardiovascular Events in Patients With Coronary Heart Disease

Abstract: Objective-The endothelium-derived fibrinolytic factor tissue plasminogen activator (t-PA) is a major determinant of vessel patency after coronary plaque rupture and thrombosis. We assessed whether endothelial fibrinolytic capacity predicts atherothrombotic events in patients with coronary heart disease. Methods and Results-Plasma t-PA and plasminogen activator inhibitor (PAI)-1 concentrations were measured during intrabrachial substance P infusion in 98 patients with angiographically proven stable coronary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 48 publications
1
40
1
Order By: Relevance
“…For example, endothelial fibrinolytic capacity, as measured by stimulated t-PA release from the forearm vasculature, predicts the future risk of adverse cardiovascular events in patients with CHD, with individuals with the lowest t-PA release experiencing the highest rate of adverse events. 26 In contrast, increased venous t-PA antigen predicts an increased risk of CHD. 27 These apparently contradictory findings may be explained by the different physiological determinants of these 2 measures of t-PA. A single measurement of venous t-PA antigen captures both free active t-PA and t-PA bound to PAI-1; because greater than 70% of t-PA circulates bound to PAI-1, increased t-PA antigen usually manifests an increase in PAI-1 rather than an increase in active t-PA. 28,29 In contrast, measurement of net release of t-PA takes the arteriovenous gradient and blood flow into account and reflects the capacity of the vascular endothelium to release stored t-PA. 30 Thus, in the current study 17␤-estradiol decreased venous t-PA antigen in parallel with PAI-1 antigen without affecting peripheral t-PA activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endothelial fibrinolytic capacity, as measured by stimulated t-PA release from the forearm vasculature, predicts the future risk of adverse cardiovascular events in patients with CHD, with individuals with the lowest t-PA release experiencing the highest rate of adverse events. 26 In contrast, increased venous t-PA antigen predicts an increased risk of CHD. 27 These apparently contradictory findings may be explained by the different physiological determinants of these 2 measures of t-PA. A single measurement of venous t-PA antigen captures both free active t-PA and t-PA bound to PAI-1; because greater than 70% of t-PA circulates bound to PAI-1, increased t-PA antigen usually manifests an increase in PAI-1 rather than an increase in active t-PA. 28,29 In contrast, measurement of net release of t-PA takes the arteriovenous gradient and blood flow into account and reflects the capacity of the vascular endothelium to release stored t-PA. 30 Thus, in the current study 17␤-estradiol decreased venous t-PA antigen in parallel with PAI-1 antigen without affecting peripheral t-PA activity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, endothelial dysfunction limits the endogenous fibrinolytic capacity and the likelihood of restoring vessel patency in the setting of an acute myocardial infarction, which can occur spontaneously in up to 30% of STEMI patients within the first 12 hours [21][22][23][24] . In keeping with this, the endothelial fibrinolytic capacity, as measured by the release of the fibrinolytic factor tissue plasminogen activator, has been found to predict the risk of future adverse cardiovascular events in patients with initially stable coronary heart disease 18 . Moreover, Lerman et al have shown that endothelial dysfunction is related to a higher incidence of consecutive acute coronary syndromes 25,26 .…”
Section: Discussionmentioning
confidence: 78%
“…In the presence of developing thrombus, endogenous fibrinolysis is rapidly initiated by the local endothelium that tightly regulates plasmin generation, fibrin degradation, and dissolution of the thrombus 18,19 . As a result, thrombus growth is limited and reperfusion is promoted; however, the efficacy of this system depends on functional endothelium 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 Of note, t-PA release and endothelium-dependent vasodilation can predict the risk of cardiovascular events. 7,8 Another important stimulus involved in modulating the fibrinolytic system 1 is adrenergic activation. 9 Because the sympathetic nervous system plays a major role in cardiovascular homeostasis and is involved in the determination of cardiovascular risk, 10 the relationship between adrenergic activation and the fibrinolytic system could be relevant in elucidating the pathophysiology of atherothrombosis.…”
mentioning
confidence: 99%